Fiber optic sensing for monitoring of corrosion and bolt loosening in metals - Yutika, Widya Tantiya (2019)
In recent years, structural health monitoring (SHM) has become more prevalent especially in civil engineering field. Various types of sensors have been used for SHM application such as strain gauge, accelerometer, etc. Plastic/ Polymer Optic Fiber (POF) sensor was selected due to its high sensitivity, low cost and ease in handling. In this project, POF sensor was utilized to monitor the failure at metallic joints and the effect of corrosion. Dynamic loading was imposed on the metallic specimen and the vibration-based measurement was carried out. In order to test corrosion, the metallic specimen was naturally corroded with rainwater and seawater while an experiment on bolts loosening was conducted to detect the failure at joints. The results were analyzed and compared to conventional method using accelerometer and simulation software ANSYS. Finally, the feasibility of this POF sensor to monitor failure at joints and corrosion was assessed.